Innovativeness of Polish industry against the global industry - Gajda, Waldemar (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The main purpose of this article is an attempt to assess the innovation of the Polish industry against the global industry. The analysis method was used in the research. The achievement of economic thought relating to innovation starting from Smith’s concept to Oslo methodology was presented in this article. The level of innovation of the Polish economy was determined with the use of statistical methods as well as indirect indicators based on the research and development intensity and direct indicators based on the results of product, process, organizational and marketing innovations. Subsequently, innovative activeness, innovative activity spending as well as revenue from sale of new products of small-, medium- and large-sized Polish enterprises were analyzed. The results were evaluated and compared with the world economy. Determinants of innovative activity of Polish industry entities indicating sources, main barriers and recommendations were determined in the conclusion on the basis of the conducted analyses and evaluations.